Data structure and algorithms - Aho, Alfred V; Ullman, Jeffrey D; Hopcroft, John E (Noida: Pearson, 2013)
About the book: An ideal book for first course on data structures and algorithms, its text ensures a style and content relevant to present-day programming. The only pre-requisite it assumes is familiarity with a high-level programming language like Pascal. The book spans cohesively across wide-ranging topics and serves as a comprehensive text for the undergraduate as well as the graduate student.
Keywords: Computer Science Engineering; Design and analysis of algorithms; Basic data types; Trees; Basic operations on sets; Advanced set representation methods; Directed & undirected graphs; Sorting; Algorithm analysis & design techniques; Data structures and algorithms for external storage; Memory management